VARNISH LAYER HARDNESS, SCRATCH RESISTANCE, AND GLOSSINESS OF VARIOUS WOOD SPECIES AS AFFECTED BY HEAT TREATMENT - Nevzat Çakıcıer; Suleyman Korkut; Derya Sevim Korkut (BioResources, 2011)
The aim of the study was to determine the effects of different heat treatment and varnish application combinations on hardness, scratch resistance, and glossiness of wood materials sampled from limba (Terminalia superba), iroko (Chlorophora excelsa), ash (Fraxinus excelsior L.), and Anatolian chestnut (Castenea sativa Mill.) species. The heat treatment was applied at two levels (150 and 180 oC) for both 3 and 6 hour periods. After the heat treatment, four types of varnish (cellulose lacquer, synthetic varnish, polyurethane varnish, and water based varnish) were applied, and hardness, scratch resistance, and glossiness of varnish film layers of the treated woods were measured. The effects of heat treatment and varnish combination applications on above mentioned variables were analyzed according to the study design (factorial design with 4 (species) x 2 (heat) x 2(duration) x 4 (varnish) = 64 experimental units) with 10 samples for each combination of parameters. Glossiness increased on wood samples for all of the four wood species treated with cellulose lacquer and synthetic varnish and across all heating treatments. However, glossiness values were decreased for all the wood species depending on heating temperature and time. Values of hardness and scratch resistance were also decreased for all the four wood species across all the treatment combinations. The results were obtained from the upper surface of the application process and are thought to contribute to the national economy.